2014
DOI: 10.1186/1471-2407-14-436
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of heme oxygenase-1 in colorectal cancer patients with increased circulation carbon monoxide levels, potentially affects chemotherapeutic sensitivity

Abstract: Background: Heme oxygenase-1 (HO-1) and its major product carbon monoxide (CO) are known to be involved in the development and progression of many tumors. The present study was to elucidate the expression and function of HO-1 in colorectal cancer (CRC), specially focusing on the circulation CO levels in CRC patients and the possible roles of HO-1 in chemoresistance of colon cancer cells. Methods: One hundred and eighteen patients received resection for colorectal cancer and polyps at China Medical University S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
73
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 51 publications
2
73
2
Order By: Relevance
“…In the HO-1-positive group, there was increased HO-1-expressing macrophages in not well-differentiated tubular adenocarcinoma (tub1) among histological types. This result was not similar to that reported by Yin et al [33]. However, there was no significant difference among histological type in the present study.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…In the HO-1-positive group, there was increased HO-1-expressing macrophages in not well-differentiated tubular adenocarcinoma (tub1) among histological types. This result was not similar to that reported by Yin et al [33]. However, there was no significant difference among histological type in the present study.…”
Section: Discussioncontrasting
confidence: 57%
“…PubMed literature records indicate that the expression of HO-1 in colorectal cancer was reported in only 4 publications [28,[32][33][34]. Kang et al [32] evaluated HO-1 protein expression levels and enzyme activity using western blotting and enzyme immunoassay and found that HO-1 protein expression and enzyme activity are higher in colonic cancer tissues than in normal tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29,30 In particular, protective autophagy plays a key role in the THP resistance of cancer cells. Moreover, THP and its prodrug epirubicin induce a cytoprotective autophagy response in bladder cancer cells 10 and breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…CRC with Hmox1 expression has a lower rate of lymphatic tumor invasion and better survival than that without [13]. Well-differentiated CRC seems to have more total but less nuclear Hmox1 expression than moderately/poorly differentiated CRC [14]. The role of Hmox1 and its interaction with the Nrf2 pathway in CRC remains uncertain.…”
Section: Introductionmentioning
confidence: 99%